Stability-indicating HPLC-PDA assay for simultaneous determination of paracetamol, thiamine and pyridoxal phosphate in tablet formulations - Ali Amir; Athar Muhammad Makshoof; Ahmed Mahmood; Nadeem Kashif; Murtaza Ghulam; Farooq Umar; Salman Muhammad (Acta Pharmaceutica)
With the increased number of multi-drug formulations, there is a need to develop new methods for simultaneous determinations of drugs. A precise, accurate and reliable liquid chromatographic method was developed for simultaneous determination of paracetamol, thiamine, and pyridoxal phosphate in pharmaceutical formulations. Separation of analytes was carried out with an Agilent Poroshell C18 column. A mixture of ammonium phosphate buffer (pH = 3.0), acetonitrile and methanol in the ratio of 86:7:7 (V/V/V) was used as the mobile phase pumped at a flow rate of 1.8 mL min−1. Detection of all three components, impurities and degradation products was performed at the selected wavelength of 270 nm. The developed method was validated in terms of linearity, specificity, precision, accuracy, LOD and LOQ as per ICH guidelines. Linearity of the developed method was found in the range 17.5–30 µg mL−1 for thiamine, 35–60 µg mL−1 for pyridoxal phosphate and 87.5–150 µg mL−1 for paracetamol. The coefficient of determination was ≥ 0.9981 for all three analytes. The proposed HPLC method was found to be simple and reliable for the routine simultaneous analysis of paracetamol, thiamine and pyridoxal phosphate in tablet formulations. Complete separation of analytes in the presence of degradation products indicated selectivity of the method.